Validating the factor structure of primary school teaching quality using the PDCA cycle - Nhat Thong Du; Van Dat Tran (Institute of Advanced Engineering and Science, 2026)
Improving teaching quality is a critical goal of educational reform, particularly in the context of Vietnam’s 2018 General Education Program (GEP). However, there is still a lack of valid instruments for assessing instructional practices based on continuous improvement models. This research fills this void by creating and validating the primary school teaching quality scale (PSTQS), based on the Plan-Do-Check-Act (PDCA) cycle, a well-known quality management framework. A cross-sectional survey design was used to collect data from 528 primary school teachers in Ho Chi Minh City. The 20-item PSTQS was constructed to align with the PDCA model and the competencies outlined in the 2018 GEP. The sample was randomly split into two groups for a two-phase validation: exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). EFA found a four-factor structure that matched the PDCA cycle and accounted for 45.3% of the variance. CFA confirmed the model’s fit (comparative fit index (CFI)=0.95, Tucker-Lewis index (TLI)=0.94, root mean square error of approximation (RMSEA)=0.04, standardized root mean square residual (SRMR)=0.05). The scale demonstrated strong internal consistency (composite reliability (CR)>0.79), with robust convergent and discriminant validity. The PSTQS is a reliable, valid tool for evaluating teaching practices through a quality improvement lens. While results are specific to Ho Chi Minh City, the scale offers a foundation for broader application and supports continuous professional development and policy implementation.